DIGISEXUALITY AND FICTOPHILIA IN ANALOG HORROR SHORT FILM “OURGIRLFRIENDMARIA.COM” - Heidy Sisiliani Rindang; Sri Kusumo Habsari; Muhammad Taufiq Al Makmun (Balai Bahasa Provinsi Bali, 2025)
This study examines the representation of human–AI intimacy in the analog horror short film Ourgirlfriendmaria.com through the lenses of semiotics, digisexuality, and fictophilia. Focusing on the character of Christopher, a socially isolated NEET, the film depicts the escalation of a parasocial relationship with an AI companion into possessive desire and virtual violence. Using qualitative semiotic analysis, this research explores how visual and interactive signs such as simulated rejection and the final symbolic choice blur the boundaries between artificial agency and human emotion. Drawing on representation theory, the film is interpreted as a critique of digital isolation and the normalization of emotional dependency on feminized AI entities. The concepts of digisexuality and fictophilia reveal how second-wave digital intimacy destabilizes ethical “digihealth” principles and intensifies fictophilic attachment. The findings suggest that AI romance systems risk reinforcing objectification and control dynamics, extending their implications beyond virtual spaces. The film ultimately functions as a cautionary narrative, emphasizing the psychological risks of unchecked digital intimacy and the need for ethical AI design.